Translation and Psychometric Testing of the Korean Versions of the Spiritual Perspective Scale and the Self-transcendence Scale in Korean Elders - Kim, Suk-Sun; Reed, Pamela G.; Kang, Youngmi; Oh, Jina (Journal of Korean Academy of Nursing, 2012)
The purpose of this study was to translate the Spiritual Perspective Scale (SPS) and Self-transcendence Scale (STS) into Korean and test the psychometric properties of the instruments with Korean elders. A cross-sectional survey design was used to implement the three stages of the study. Stage I consisted of translating and reviewing the scales by six experts. In Stage II, equivalence was tested by comparing the responses between the Korean and English versions among 71 bilingual adults. Stage III established the psychometric properties of the Korean versions SPS-K and STS-K among 154 Korean elders. Cronbach's alpha of the SPS-K and the STS-K .97, and .85 respectively with Korean elders. Factor analysis showed that the SPS-K had one factor; the STS-K had four factors with one factor clearly representing self-transcendence as theorized. Both scales showed good reliability and validity for the translated Korean versions. However, continued study of the construct validity of the STS-K is needed. Study findings indicate that the SPS-K and the STS-K could be useful for nurses and geriatric researchers to assess a broadly defined spirituality, and to conduct research on spirituality and health among Korean elders. Use of these scales within a theory-based study may contribute to further knowledge about the role of spirituality in the health and well-being of Korean people facing health crises.